Dictionnaire des Finances - Say, Léon (Quarterly Journal of Economics, 1887)
Journal Article Dictionnaire des Finances Get access The Quarterly Journal of Economics, Volume 1, Issue 2, January 1887, Page 223, https://doi.org/10.1093/qje/1.2.223-a Published: 01 January 1887